(3eHGOF GdGbJUGO GdLRFjs (3JMdjd fXQj hJWHjbjs - (3Hhjgj(B, (3eMeOs ((3GdLRGFQs (3GdHOQ GdSGWYs, 2010)
(3jMJhj gPG GdcJGH Ydi CQHYI CHhGH ChdgG JeKd aj fXQjI GdWdH heQhfJg HGdEVGaI Edi OGdI GdYQV heQhfJg, eY fXQjI GdKef, GdEFJeGf aj GdMjGI GdYedjI hCKQ JONd GdMcheI aj GdCShGb, hcPdc fXQjI GdefaYI GdMOjI GdJj JMOK YfgG aj GdHGH GdKGfj, eY fXQjI efMfjGJ GdShGA HGdEVGaI Edi CKQ GdONd(B- (3CKQ GdEMdGd(B- (3CKQ GdKef(B. (3CeG aj GdHGH GdKGdK aYQV dfG fXQjI GdGfJGL hfXQjI JcGdja GdGfJGL(B- (3fabGJ GdGfJGL(B-. (3eY fXQjI GdGjQGOGJ(B.(3CeG GdHGH GdQGHY hGdCNjQ abO MOKfG Yf JhGRf GdeDSSI aj Shb GdefGaSI GdJGeI hJhGRfgG aj Shb GdGMJcGQ GdcGed eY GdefGaSI GdGMJcGQjI hGdGMJcGQ GdeJYOO hGMJcGQ GdbdI(B.s
Keywords: (3GdEbJUGO GdLRFjs